Combating Misinformation and Polarization in the Corporate Sphere: Integrating Social, Technological and AI Strategies. - Tejero, Alberto; Pisoni, Galena; Habibi Lashkari, Ziba; Rios Aguilar, Sergio (International Journal of Interactive Multimedia and Artificial Intelligence, 2025)
In an era where misinformation and polarization present significant challenges, this research examines the root causes within social networks and assesses how corporations can use AI technologies for prompt detection. This research uses a dual approach: a "telephone game" with 225 participants from a Spanish university to study the spread of misinformation, and interviews with 15 experts from three French tech companies to investigate technological solutions. The findings indicate that almost one-third of participants inadvertently contribute to polarization, and around one-quarter propagated misinformation. The study also identifies the existing tools enhanced by AI and Machine Learning that effectively detect misinformation and polarization in corporate settings. This investigation provides crucial insights for practitioners to strengthen their strategies against misinformation and technical challenges and opportunities.